Knowledge, Attitude and Preventive Practice Regarding the COVID-19 among the Mothers Attending in Shree Birendra Hospital - Bhele, Rajya Laxmi; Mulepati, Sumitra (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: COVID-19 is an infectious disease caused by the SARS-CoV-2 virus. The virus might spread through respiratory droplets or close contact. Compared to the general population, mothers have a higher chance of developing serious illnesses from COVID-19. The study aims to identify knowledge, attitudes, and preventive practices regarding COVID-19 among mothers. Methods: A descriptive, cross-sectional study was conducted at Shree Birendra Hospital. Nonprobability convenience sampling technique was used. The sample size was 385. A structured, self-administered questionnaire was developed. Ethical approval was received and written, informed consent was obtained from each respondent. Microsoft Excel and SPSS Version 22 were used for data entry and analysis. The statistics used were frequency, percentage, Pearson’s correlation coefficient, and Fisher’s exact test. Results: Of the total 385 respondents, 50.9% had good knowledge, 57.7% had positive attitudes, and 72.2% had good preventive practices. There was significant positive correlationbetween knowledge, attitudes, and practices. Pregnant mothers had higher levels of knowledge compared to lactating mothers. Mothers with higher education levels demonstrated better knowledge. Mothers without a disease tended to have more positive attitudes. Conclusions: The study concludes thatmore than half of the mothers had good knowledge, a positive attitude, and good preventive practices about COVID-19. Significant positive correlation was found between the knowledge, attitudes, and preventive practices of mothers.